Seizures due to multiple sclerosis: seven patients with MRI correlations. - Thompson, A J (1993)
The MRI data of seven patients with clinically definite multiple sclerosis who developed epileptic seizures are presented. Six of these cases demonstrated new or enhancing lesions. Cerebral biopsy in one of these lesions confirmed inflammation with myelin breakdown products. Lesions implicated in the causation of seizures involved the cortex or subcortical area. In one patient, a new lesion was associated with EEG abnormalities which resolved as the lesion reduced in size. In three patients epileptic activity was the only clinical manifestation of disease. Large, unresolving lesions tended to be associated with continuing seizures.